The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fpls.2017.00249
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on Biomass and Regeneration of Vegetation in a Geothermal Area

Abstract: Understanding the effects of increasing temperature is central in explaining the effects of climate change on vegetation. Here, we investigate how warming affects vegetation regeneration and root biomass and if there is an interactive effect of warming with other environmental variables. We also examine if geothermal warming effects on vegetation regeneration and root biomass can be used in climate change experiments. Monitoring plots were arranged in a grid across the study area to cover a range of soil tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 86 publications
3
9
0
Order By: Relevance
“…Earlier studies have shown that temperature is a major factor altering plant phenotypic traits as it influences growth as well as the timing of plant development (Cleland, Chuine, Menzel, Mooney, & Schwartz, ; Hatfield & Prueger, ). A negative correlation between plant biomass or plant height and temperature, as found in our study, has already been shown in Silene noctiflora (Qaderi & Reid, ) and Erigeron speciosus (De Valpine & Harte, ) and was also observed for vegetation cover in geothermal areas (Nishar et al., ). Reduced plant height and smaller leaves result in a smaller transpiration surface and thus may help the plant to withstand the increased drought stress at higher temperatures.…”
Section: Discussionsupporting
confidence: 89%
“…Earlier studies have shown that temperature is a major factor altering plant phenotypic traits as it influences growth as well as the timing of plant development (Cleland, Chuine, Menzel, Mooney, & Schwartz, ; Hatfield & Prueger, ). A negative correlation between plant biomass or plant height and temperature, as found in our study, has already been shown in Silene noctiflora (Qaderi & Reid, ) and Erigeron speciosus (De Valpine & Harte, ) and was also observed for vegetation cover in geothermal areas (Nishar et al., ). Reduced plant height and smaller leaves result in a smaller transpiration surface and thus may help the plant to withstand the increased drought stress at higher temperatures.…”
Section: Discussionsupporting
confidence: 89%
“…Resource usage by the consumer community thus seemingly kept pace with resource provisioning, with no overall change in percentage cover of the vegetation community as soil temperature increased. Faster rates of vegetation regeneration at higher temperatures (Nishar et al., ) may play a key role in meeting the higher metabolic demands of herbivores and subsequently their predators. Arctic and subarctic organisms are also predicted to exhibit relatively small absolute shifts in metabolic rate compared to those at lower latitudes due to their cooler baseline temperatures and the exponential relationship between metabolism and temperature (Dillon, Wang, & Huey, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ecological vegetation restoration is an effective method for controlling soil erosion, a strenuous task that needs to be executed over long time periods in the loess hilly region [3,4]. Soil water and heat are important factors that influence vegetation development, characterized using soil moisture and temperature [5,6]. Therefore, investigating the variability in soil moisture and temperature is important for vegetation restoration in the loess hilly region.…”
Section: Introductionmentioning
confidence: 99%